The Influence of Traditional Games on The Agility of Rugby Athletes in Sumedang Regency - Fauzan Hernanda Putra; Dinar Dinangsit; Encep Sudirjo (Journal of Physical Education Health and Sport, 2026)
This research is motivated by the importance of improving the physical condition component, especially agility, in rugby and the need for innovative and non-monotonous training methods. Traditional games are seen as an interesting and effective alternative to exercise because they have dynamic movement characteristics. The purpose of this study is to determine the influence of traditional games on the increase in the agility of rugby athletes in Sumedang Regency and the amount of contribution given. This study uses a quantitative approach with experimental methods and one group pretest-posttest design. The research sample amounted to 10 rugby athletes who were selected using the purposive sampling technique. The instrument used is the Illinois Agility Test to measure the level of agility of athletes. Treatment was given through a traditional game training program (boy-boyan, galah salt, and ucing bancakan) for 12 meetings. Data analysis was carried out using descriptive and inferential statistics with paired sample t-tests. The results showed a significant increase in athletes' agility after being given treatment, with a significance value of 0.000 < 0.05. This shows that traditional games have a significant effect on the increase in the agility of rugby athletes. Thus, traditional games can be used as an effective alternative method of exercise, not only to improve physical ability, but also to increase motivation and reduce boredom in the training process.